Prototype of Wind Power Plant Using a Laboratory-Scale Vertical Axis Savonius Turbine - Ali Satria Wijaya; Fiqri Al Faruqi; Imas Ning Zhafarina; Pertiwi Nurul Utami; Andicho Haryus Wirasapta (Jurnal Edukasi Elektro, 2026)
This study investigates the performance of a laboratory-scale vertical-axis Savonius wind turbine prototype developed based on a simple and robust mechanical design for small-scale renewable energy applications. The prototype frame was constructed using angle steel with a cross-section of 40 × 40 mm and a thickness of 1.8 mm, forming a rectangular structure with overall dimensions of 150 cm × 150 cm and a height of 50 cm. The Savonius rotor employed a solid steel shaft with a diameter of 2.5 cm and acrylic blades measuring 100 cm in height and 40 cm in width. Performance data were collected over a six-month observation period from August 2025 to January 2026 under low to moderate wind speed conditions. The measured wind speed ranged from approximately 3.5 to 6.5 m/s, resulting in power outputs between 0.77 W and 9.44 W. The calculated power coefficient (Cp) varied from 0.18 to 0.34, indicating a typical efficiency range for drag-based Savonius turbines. The results show a consistent increase in rotor speed and electrical power output with rising wind speed, while Cp values tend to stabilize at higher wind velocities, reflecting aerodynamic performance limitations inherent to Savonius turbines. These findings demonstrate that the developed prototype exhibits stable and predictable behavior, making it suitable for laboratory experimentation, educational purposes, and preliminary assessment of small-scale wind energy systems operating in low wind speed environments.